Studies on trypanosome-resistant cattle. II. The effect of trypanosomiasis on N'Dama, Muturu and zebu cattle - Roberts, C.J.; Gray, A.R. (Springer, 1973)
The effects of trypanosomiasis and production of zebu, N'Dama and Muturu cattle in tse-tse infested areas are investigated. Observations on parasitaemia, blood values, body weight and clinical condition included. The zebu, N'Dama and Muturu cattle showed relative resistance to infection with trypanosomes transmitted by glossina morsitans submorsitans. Data on their productivity in livestock development projects in tsetse infected areas are included.